THE USE OF VLOG AS A MEDIA FOR ENHANCING TENTH GRADERS HOSPITALITIES SPEAKING SKILL AT SMKN 8 SURABAYA - Agustin, Felza Wiranadya (JOEEL (Journal of English Education and Literature), 2022)
The purpose of this study was to describe the students speaking improvement after the implementation of Vlog as a medium in teaching and learning process. The subject of this research were the students at the tenth grade hospitality 1 of SMKN 8 Surabaya in the academic year 2021/2022, which consisted of 35 students. The method in this study was Classroom Action Research that completed within 2 cycles. Each cycles following the four phases in cyclical namely planning, acting, observing and reflecting. However, a different treatment was given in the second cycle for a better result. Based on the data, the students showed significant improvement in their speaking performance after the second cycle conducted. In the first cycle, only a few well engaged to the learning process. When performing their speaking skill, they still makes some pauses and mispronounce words. The scores showed only 60% of students met the minimum standard or KKM. In the second cycle, through revisions based on the first cycle, the students could speak more fluently and accurately, and it can be seen from 91% of students who can improve their score above the minimum criteria of mastery speaking. In conclusion, Vlog can be an alternative and innovative media to enhance the students speaking skill.